If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 4y = 53 Solving 3x + 4y = 53 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4y' to each side of the equation. 3x + 4y + -4y = 53 + -4y Combine like terms: 4y + -4y = 0 3x + 0 = 53 + -4y 3x = 53 + -4y Divide each side by '3'. x = 17.66666667 + -1.333333333y Simplifying x = 17.66666667 + -1.333333333y
| 8x-23=7x+17 | | 6=z(10-z) | | 196x^2+49x+2=0 | | 1.054(2001)-2088= | | 2t-301/5=20 | | 3x+10=30-2x | | 5a+a=42 | | y=1.9 | | 1.054(1996)-2088= | | (1/29)=3 | | 2x-6x+3=x-5+8 | | 6x=x+288 | | 1.054(1992)-2088= | | 7x-2+9x=6x-8 | | (2x-3)=2(4x+1) | | 4(x-6)=52 | | 24=(2x)-(3x-1) | | 0.8x=0.16 | | 1.5x^2+3x-12=0 | | -3(a+5)-10(1-6a)= | | 11x+8=1x+48 | | 6(a-2b)-3(2a+b)= | | 0.16xn=74 | | (7x+6)-(-8x+9)= | | -2x-13=6 | | 3.5x(2x+3)-3x(x+1.5)= | | 1000z^3-1=0 | | 6-5p=-7p+3p | | 3(-2-3x)=-8x-4 | | y+0.4=0.6y+1.2 | | -128-8y=-48 | | 5n^2+5n=6 |